How to ensure threatened species monitoring leads to threatened species conservation. (31st August 2018) - Robinson, Natasha M.; Scheele, Ben C.; Legge, Sarah; Southwell, Darren M.; Carter, Oberon; Lintermans, Mark; Radford, James Q.; Skroblin, Anja; Dickman, Chris R.; Koleck, Jessica; Wayne, Adrian F.; Kanowski, John; et al.
Summary: Monitoring is essential for effective conservation and management of threatened species and ecological communities. However, more often than not, threatened species monitoring is poorly implemented, meaning that conservation decisions are not informed by the best available knowledge. We outline challenges and provide best‐practice guidelines for threatened species monitoring, informed by the diverse perspectives of 26 conservation managers and scientists from a range of organisations with expertise across Australian species and ecosystems. Our collective expertise synthesised five key principles that aim to enhance the design, implementation and outcomes of threatened species monitoring. These principles are (i) integrate monitoring with management; (ii) design fit‐for‐purpose monitoring programs; (iii) engage people and organisations; (iv) ensure good data management; and (v) communicate the value of monitoring. We describe how to incorporate these principles into existing frameworks to improve current and future monitoring programs. Effective monitoring is essential to inform appropriate management and enable better conservation outcomes for our most vulnerable species and ecological communities.